Mental Health Challenges of United States Healthcare Professionals During COVID-19 - Pearman, Ann; Hughes, MacKenzie L.; Smith, Emily L.; Neupert, Shevaun D. (Frontiers in Psychology, 2020)
As COVID-19 continues to impact global society, healthcare professionals are at risk for a number of negative well-being outcomes due to their role as care providers. The objective of this study was to better understand the current psychological impact COVID-19 on healthcare professionals in the U.S. This study used an online survey tool to collect demographic data and measures of well-being of adults age 18 and older living in the U.S. between March 20, 2020 and May 14, 2020. Measures included anxiety and stress related to COVID-19, depressive symptoms, current general anxiety, health questions, tiredness, control beliefs, proactive coping, and past and future appraisals of COVID-related stress. The sample included 90 healthcare professionals and 90 age-matched controls (Mage = 34.72 years, SD = 9.84, range = 23 – 67) from 35 U.S. states. A multivariate analysis of variance was performed, using education as a covariate, to identify group differences in the mental and physical health measures. Healthcare professionals reported higher levels of depressive symptoms, past and future appraisal of COVID-related stress, concern about their health, tiredness, current general anxiety, and constraint, in addition to lower levels of proactive coping compared to those who were not healthcare professionals (p < .001, η2 = .28). Within the context of this pandemic, healthcare professionals were at increased risk for a number of negative well-being outcomes. Potential targets, such as adaptive coping training, for intervention are discussed.